Design Expert-Implemented Nimodipine-Loaded Lyophilized Nanoemulsifying Drug Delivery System for Improved Oral Bioavailability and Physical Stability - Das, Prativa; Panda, Jnyanaranjan; Jena, Goutam Kumar; Patra, Chinam Niranjan; Panigrahi, Kahnu Charan (Indian Journal of Pharmaceutical Education and Research, 2024)
Purpose: To improve the oral bioavailability as well as the physical stability of nimodipine, Design-Expert-driven nimodipine loaded nanoemulsifying drug delivery system was developed with a certain quality target product profile. Materials and Methods: In this investigation, the three components triacetin as oil phase, labrasol as a surfactant, and plurol oleique CC 497 as co-surfactant were selected after screening. The ratio of surfactant and co-surfactant (Smix) was selected from the pseudo-ternary phase diagram drawn by using ProSim ternary software. A d-optimal mixture design was employed to optimize the formulation. The dynamic light scattering, Fourier transform Infrared, Differential Scanning Calorimetry, X-ray Diffraction, Scanning Electron Microscopy, in vitro drug release, stability study, and in vivo pharmacokinetic studies were carried out for the characterization of the optimized formulation. Results: The globule size, PDI, and Zeta potential of the optimized formulation were found to be 322.1 nm, 0.48, and -14.5 mV respectively. The result of in vivo pharmacokinetic studies exhibited three-fold enhanced oral bioavailability of the optimized nanoemulsion as compared to the pure drug of nimodipine and the physical stability of the optimized nanoemulsion improved significantly as compared to the pure drug. Conclusion: The NIMO-loaded nanoemulsifying drug delivery system can be successfully fabricated by implementing the Design-Expert with improved oral bioavailability and physical stability significantly as compared to the pure drug of NIMO.
Keywords: Bioavailability; Physical stability; Pseudo ternary phase diagram; Design-Expert; Lyophilized; Nanoemulsifying drug delivery system